2016
DOI: 10.18632/oncotarget.11710
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of thyroid nodules increases shear-wave speed (SWS) measurement: using multiple calcification-specific SWS cutoff values outperforms a single uniform cutoff value in diagnosing malignant thyroid nodules

Abstract: Conventional ultrasound cannot satisfactorily distinguish malignant and benign thyroid nodules. Shear-wave elastography (SWE) can evaluate tissue stiffness and complement conventional ultrasound in diagnosing malignant nodules. However, calcification of nodules may affect the results of SWE. The purposes of this study are to compare the differences of shear-wave speed (SWS) measurement among different calcification groups and compare the diagnostic performance between using a single uniform SWS cutoff value an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…We found that the presence of macrocalcifications on B-mode ultrasound imaging increased SWS in malignant thyroid nodules. This was an expected finding and consistent with prior studies, as intra-nodular calcifications are known to affect lesion stiffness (Gregory et al, 2015;Chen et al, 2016;Sun et al, 2017). Interestingly, we found that peripheral rim calcifications did not significantly affect SWS in either benign or malignant thyroid nodules.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the presence of macrocalcifications on B-mode ultrasound imaging increased SWS in malignant thyroid nodules. This was an expected finding and consistent with prior studies, as intra-nodular calcifications are known to affect lesion stiffness (Gregory et al, 2015;Chen et al, 2016;Sun et al, 2017). Interestingly, we found that peripheral rim calcifications did not significantly affect SWS in either benign or malignant thyroid nodules.…”
Section: Discussionsupporting
confidence: 92%
“…CT has high-density resolution in the diagnosis of lung cancer and can avoid overlapping of chest wall, heart, and mediastinum. Many small lesions in hidden parts of the lung can be found, which is of great help in judging the scope of lesions and disease staging [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the Emax values in Groups B and C had high diagnostic sensitivity, consistent with the pathological development process of thyroid cancer, and these values were slightly higher than the results of previous research 18 , which may be related to the inclusion and exclusion criteria. This study excluded internal or peripheral nodules with coarse calcification, a decision that was based on previous studies 23 showing that calcification can increase Emax. This is one of the main reasons for the high false-positive rate of SWE-based diagnosis of malignant nodules.…”
Section: Discussionmentioning
confidence: 99%